PENGEMBANGAN E-LKPD BERBANTUAN TOPWORKSHEETS MATERI TEKS NEGOSIASI PADA SISWA KELAS X - Indah Sari, Maya; Rosmawaty, Rosmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is 1) to explain the process of developing E-LKPD assisted by Topworksheets on negotiation text material for class X students; 2) to determine the form of development of E-LKPD assisted by Topworksheets on negotiation text material for class X students; 3) to determine the feasibility of E-LKPD assisted by Topworksheets on negotiation text material for class X students based on the results of expert validation and small group trials on students. This study is a type of research and development (R&D). The design of this study uses the ADDIE development model which is focused on 3 main stages, namely: Analysis, Design, and Development. Data collection techniques in this study are interviews, questionnaires, observations, and document analysis. Limited trial subjects were conducted on 10 class X-11 students. Data were analyzed using qualitative and quantitative descriptive analysis. The results of this study are 1) The process of developing E-LKPD assisted by Topworksheets on negotiation text material for class X students through the stages of analysis, design, and development. 2) The form of development is in the form of an E-LKPD product assisted by Topworksheets of negotiation text material which is systematically arranged consisting of the initial part (cover, concept map, and usage instructions), the content part (learning material), the interactive practice or assessment part, and learning reflection. 3) The feasibility of the developed E-LKPD is stated to be very suitable for use in learning based on the validation results of material experts, namely 94,78%, media experts 96,25%, and student responses 93,56%.